Synthesis, characterization and electrical properties of peripherally tetra-aldazine substituted novel metal free phthalocyanine and its zinc(II) and nickel(II) complexes - DUMLUDAĞ, FATİH (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
The novel phthalonitrile containing azine segment and its corresponding tetra aldazine substituted metal free- and metallo-phthalocyanines (Zn(II) and Ni(II)) were synthesized and characterized by IR, H-1 NMR, Mass, UV-Vis spectroscopy and elemental analysis and addition to these techniques for substituted phthalonitrile C-13 NMR have been used. In addition, dc and ac electrical properties of the films of these novel phthalocyanines were investigated as a function of temperature (295-523 K) and frequency (40-10(5) Hz). Activation energy values of the films of the phthalocyanines were calculated from straight portions of the Arrhenius plot (ln sigma(dc)-1/T curves) as 0.70 eV, 0.93 eV and 0.91 eV for the films of metal free, nickel- and zinc-phthalocyanines, respectively. From impedance spectroscopy measurements, it is observed that bulk resistance decreases with increasing temperature indicating semiconductor property. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Electrical characterization; Impedance spectra; Hopping; Semiconductor; Conductivity; MICROWAVE-ASSISTED SYNTHESIS; HYDRAZIDE/HYDRAZONE DERIVATIVES; POLYMERIC PHTHALOCYANINES; AC CONDUCTION; SCHIFF-BASE; THIN-FILMS; METALLOPHTHALOCYANINES; SEMICONDUCTORS; MOIETIES; SENSORS